Downregulation of Vascular Hemeoxygenase-1 Leads to Vasculopathy in Systemic Sclerosis - Ross, Rebecca L; Mavria, Georgia; Del Galdo, Francesco; Elies, Jacobo (Frontiers in Physiology, 2022)
Systemic sclerosis (SSc) is a terminal disease characterised by vasculopathy, tissue fibrosis, and autoimmunity. Endothelial dysfunction, oxidative stress, and calcium handling dysregulation have been associated with a large number of SSc-related complications. Hemeoxygenase-1 (HO-1) is an antioxidant enzyme involved in multiple biological actions in the cardiovascular system including vascular tone, angiogenesis, cellular proliferation, apoptosis and oxidative stress. The aim of this work was to investigate the physiological role of HO-1 and its relevance in the cardiovascular complications occurring in SSc. Our results indicate that HO-1 regulates calcium release from intracellular stores of human pulmonary arterial endothelial. We interrogated the activity of HO-1 in angiogenesis using an organotypic co-culture of fibroblast-endothelial cell. Inhibition of HO-1 significantly reduced the ability of endothelial cells to form tubules. We further investigated if this could be associated with cell motility or migration of endothelial cells into the extracellular matrix synthesised by fibroblasts. By mean of holographic imaging, we studied the morphological and functional features of endothelial cells in the presence of an HO-1 activator and selective inhibitors. Our results demonstrate that inhibition of HO-1 significantly reduces cell proliferation and cell motility (migration) of cultured endothelial cells, whilst activation of HO-1 does not modify either morphology, proliferation or motility. In addition, we investigated the actions of CO on the Kv7.1 (KCQN1) channel, an important component of the cardiac action potential repolarization. Using electrophysiology (whole-cell patch-clamp in a recombinant system overexpressing the KCQN1 channel), we assessed the regulation of KCQN1 by CO. CORM-2, a CO donor, significantly reduced the Kv7.1 current, suggesting that HO-1/CO signalling may play a role in the modulation of the cardiac action potential via regulation of this ion channel. In summary, our results indicate a clear link between downregulation of HO-1/CO signalling and pathophysiological processes occurring in early phases of SSc, such as calcium homeostasis dysregulation, impaired angiogenesis and cardiac arrhythmias. A better understanding of the canonical actions (mainly due to the biological actions of CO), and non-canonical actions of HO-1, as well as the interaction of HO-1/CO signalling with other gasotransmitters in SSc will contribute to the development of novel therapeutic approaches.